Exploring the potential of metal and metal oxide nanomaterials for sustainable water and wastewater treatment: A review of their antimicrobial properties - Kamyab H.; Chelliapan S.; Hayder G.; Yusuf M.; Taheri M.M.; Rezania S.; Hasan M.; Yadav K.K.; Khorami M.; Farajnezhad M.; Nouri J. (Elsevier Ltd, 2024)
Metallic nanoparticles (NPs) are of particular interest as antimicrobial agents in water and wastewater treatment due to their broad suppressive range against bacteria, viruses, and fungi commonly found in these environments. This review explores the potential of different types of metallic NPs, including zinc oxide, gold, copper oxide, and titanium oxide, for use as effective antimicrobial agents in water and wastewater treatment. This is due to the fact that metallic NPs possess a broad suppressive range against bacteria, viruses, as well as fungus. In addition to that, NPs are becoming an increasingly popular alternative to antibiotics for treating bacterial infections. Despite the fact that most research has been focused on silver NPs because of the antibacterial qualities that are known to be associated with them, curiosity about other metallic NPs as potential antimicrobial agents has been growing. Zinc oxide, gold, copper oxide, and titanium oxide NPs are included in this category since it has been demonstrated that these elements have antibacterial properties. Inducing oxidative stress, damage to the cellular membranes, and breakdowns throughout the protein and DNA chains are some of the ways that metallic NPs can have an influence on microbial cells. The purpose of this review was to engage in an in-depth conversation about the current state of the art regarding the utilization of the most important categories of metallic NPs that are used as antimicrobial agents. Several approaches for the synthesis of metal-based NPs were reviewed, including physical and chemical methods as well as green synthesis approaches, which are synthesis procedures that do not involve the employment of any chemical agents. Moreover, additional pharmacokinetics, physicochemical properties, and the toxicological hazard associated with the application of silver NPs as antimicrobial agents were discussed. 2023 Elsevier Ltd